Analytical Value of Cell-Free DNA Based on Alu in Psychiatric Disorders - Qi, Jing; Chen, Ling-Yun; Shen, Xian-Juan; Ju, Shao-Qing (Frontiers in Psychiatry, 2020)
Psychiatric disorders impose a huge burden on individuals, families, and society. The Alu repeat sequence is a member of the short interspersed nulear element (SINE) family of mammalian genomes, however, its expression pattern and role in psychiatric disorders is unclear. The current paper aimed at determining the concentrations of Alu in patients with schizophrenia (SZ), major depressive disorder (MDD) and alcohol-induced psychotic disorder (AIPD), and to further define the role and value of Alu as a potential biomarker in psychiatric disorders. In this work, we found that the concentration of Alu was considerably incremented in patients with SZ, and a significant difference existed between patients diagnosed with SZ and MDD or AIPD. ROC analysis also indicated that Alu was effective in the complementary diagnosis of SZ, and differentially diagnosed between SZ patients and patients with MDD or AIPD. In addition, we found a positive relationship between the Alu concentrations and interleukin-1β (IL-1β) in patients with SZ, MDD, and AIPD, and between the concentrations of Alu and interleukin-18 (IL-18) in patients with SZ. Overall, the present work indicates that Alu might be an innovative biomarker for diagnosing psychiatric disorders, and provides the basis for hypotheses about the pathophysiology of psychiatric disorders.